Descriptor-based identification of bimetallic-derived catalysts for selective activation of ethane with CO2. Issue 1 (11th November 2022) - Guo, Haoyue; Xie, Zhenhua; Wang, Xuelong; Chen, Jingguang G.; Liu, Ping
Abstract : Ethane–CO2 reaction over a wide range of bimetallic-derived catalysts was adopted to unravel the structure–function relationship over two types of representative structures. Abstract : The selective activation of ethane with CO2 offers a promising strategy to simultaneously reduce the greenhouse gas and upgrade the underutilized ethane to value-added chemicals. Herein, the catalytic reactions of ethane and CO2 over a series of indium (In)-based bimetallic-derived catalysts were investigated by combining catalytic evaluation, in situ characterization and Density Functional Theory (DFT) calculations. The DFT-calculated energetics along the dry reforming of ethane pathway to produce syngas and oxidative dehydrogenation of ethane to produce ethylene were consistent with the trend in experimentally observed selectivity. Combining the results currently collected for In-based bimetallic catalysts with those previously reported for other bimetallic systems, a descriptor-based model was used to scale the ethylene selectivity over a wide range of bimetallic systems. Furthermore, results from the current study enhanced the mechanistic understanding of the importance that the binding strength of the initial reaction intermediates played in controlling the selective activation of ethane with CO2 .